PENGARUH MOTIVASI KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL STUDI KASUS PADA GURU MADRASAH ALIYAH DI KECAMATAN WINONG KABUPATEN PATI - Endah Susilowati, 12.5202.0215 (Jurnal Mahasiswa Pasca Sarjana, 2016)
This study aims to examine and analyze whether the effect of workmotivation and teacher competence on teacher performance transformationalleadership moderated Principal at Madrasah Aliyah teacher in District WinongPati regency.Sampling was done by census method so that all teachers who worked inMadrasah Aliyah in District Winong of Pati regency, amounting to 83 people asrespondents. Mechanical testing of the data used in this study include testing thevalidity of the factor analysis, reliability testing with Cronbach alpha formula,multiple regression analysis, and the significance test, the coefficient ofdetermination to prove the truth of the hypothesis of research and testingmoderation.The results showed that; work motivation has positive and significant effecton teachers performance, teacher competence has positive and significant impacton teacher performance, transformational leadership has positive and significantimpact on teacher performance, the effect work motivation on teachers'performance moderated by transformational leadership, and the influence ofteacher competence on teachers’ performance moderated by transformationalleadership at Madrasah Aliyah in District Winong of Pati regency.Keywords: work motivation, teacher competence, transformational leadership,teacher performance